The Implementation of Islamic Religious Education Learning Management in Realizing Religious Culture - Subandi; Sa’idy; Sunarto; Muhammad Muchsin Afriyadi; Sela Kholidiani (Bulletin of Science Education, 2024)
The aim of this research is to describe and analyze teachers' abilities in planning, organizing, implementing and evaluating in the management of Islamic Religious Education (PAI) learning at SMAN 1 and SMKN 1 in East Lampung. Thus, this research uses a qualitative descriptive approach, with a case study type design. Data collection techniques uses Observation, interviews and documentation. Then the data was analyzed in two stages, namely: individual case data analysis and cross-case data analysis. The results show that the first, the basic religious thinking was developed at SMAN I and SMKN I East Lampung by practicing the religious values that are believed and carried out in daily life, and utilizing additional hours in extracurricular activities. Secondly, The pattern of implementation of PAI learning management is very unique, such as the implementation of religious culture at SMAN 1East Lampung through the 3 S culture (smile, greeting and the culture of greetings, excuse me, sorry and thank you, as well as complete reading and writing of the Koran, midday prayers, noon prayers in congregation, istighosah and group prayers, commemoration of Islamic holidays, imtaq and tadarrus activities of the Koran, joint prayers at the beginning and end of lessons, handshakes between school members, wearing of Muslim clothing by Muslim women. Thirdly, there are religious activities every Islamic holiday, such as: holding competitions in the art of reading the Koran, quizzing about religion, reading poetry or translations of the Koran, practicing prayers, fashion shows, sacrifices on Idhul Adha, fast Islamic boarding schools in the month of Ramadan and others